The role of pharmaceutical companies toward a sustainable health approach in a globalized world. (c2013) - Arzoumanian, Christine (2016)
This paper focuses on the effect of globalization and western hegemony, and its manifestations on pharmaceutical industry that is closely linked to global health conditions in the world. On a more specific note, Lebanon is one of the numerous developing countries directly implicated by the globalization of public health and its industry. This thesis examines the ability of small nation states to develop sound health policies without being influenced by powerful global pharmaceutical industries. Based on existing survey data and in-depth interviews with key stakeholders in key pharmaceutical companies, Lebanese Ministry of Public Health, and relevant syndicates this thesis reveals major challenges and opportunities for the advancement of the Lebanese public health system. Findings point to the centrality of civil society to provide critical oversight roles over public-international partnerships agreements. Civil society’s abilities to influence health policy agenda and provide early public warnings about health threats and appropriate responses represent a national safeguard for global engagement. Lebanese civil society’s “Think Again”, a part of the National Cervical Cancer Prevention Campaign, implemented in collaboration with the Ministry of Public Health and the international pharmaceutical companies demonstrates best practices in this sector.